2000
DOI: 10.1021/la9913046
|View full text |Cite
|
Sign up to set email alerts
|

Potential-Assisted Deposition of Alkanethiols on Au:  Controlled Preparation of Single- and Mixed-Component SAMs

Abstract: The commonly used method of preparing RS/Au self-assembled monolayers (SAMs) involves a passive incubation process in a nonabsorbing solvent. Preparation of mixed-component SAMs is particularly problematic under these conditions. The time course of the open circuit potential in the passive adsorption experiment suggests that control of the deposition potential could lead to a faster and ultimately more complete SAM formation process. This is shown to be the case, as both C16 RS/Au SAMs and mixed C16/HOOCC15S/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
117
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 41 publications
4
117
0
Order By: Relevance
“…The dsDNA immobilization on gold can be controlled by electric potential. For instance, faster formation of a more compact layer of the thiolated ssDNA was achieved under application of low positive potential (+0.2 V vs. SCE) [57].…”
Section: Commentsmentioning
confidence: 99%
“…The dsDNA immobilization on gold can be controlled by electric potential. For instance, faster formation of a more compact layer of the thiolated ssDNA was achieved under application of low positive potential (+0.2 V vs. SCE) [57].…”
Section: Commentsmentioning
confidence: 99%
“…[10][11][12][13][14] Self-assembled monolayers (SAMs) are formed at a solidliquid interface by molecules consisted of three units: a headgroup that binds to the substrate, a tailgroup that constitutes the outer surface of the film, and a backbone, usually a long chain, that connects the headgroup and the tailgroup. While pure alkylthiols are known to form SAMs that exhibit order on a large scale, [15][16][17][18] -conjugated thiols and their derivatives seem to be a better choice for applications in organic-and single-molecule electronics because of their intrinsic semiconducting properties. Relatively recently, Piotrowski et al 19 reported the synthesis and electronic properties of thioacetate-functionalized fullerene, Park et al 20 studied the formation of octylthioacetates SAMs on gold in the vapor phase.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] One of the challenges in the development of more efficient biofuel cells is to perform multistep oxidation of a fuel such as glucose to enhance the power output of the cell. 5 Enzymatic biofuel cells in particular face a 20 significant limitation in this regard due to the specificity of enzymes, limiting their use to single substrates. Enzyme cascades can alleviate this limitation by enabling the sequential and more complete oxidation of the fuel.…”
mentioning
confidence: 99%
“…Application of an appropriate potential can also be used for the rapid formation and desorption of SAM layers, with electrode modification occurring on time scales of 70 minutes as opposed to the longer time scales (hours) used for solution deposition. [17][18][19][20][21] Typically, SAM formation is performed in nonaqueous solutions, due to the limited solubility of thiols in aqueous buffer. An example of the electrochemically promoted adsorption and desorption of an alkanethiol is that of 75 dodecanethiol in a solution containing 0.5 M KOH in aqueous ethanol.…”
mentioning
confidence: 99%
See 1 more Smart Citation